Relevance of the Axis Spermidine/eIF5A for Plant Growth and Development - Belda-Palazón, Borja; Almendáriz, Carla; Martí, Esmeralda; Carbonell, Juan; Ferrando, Alejandro (Frontiers in Plant Science, 2016)
One key role of the essential polyamine spermidine in eukaryotes is to provide the 4-aminobutyl moiety group destined to the post-translational modification of a lysine in the highly conserved translation factor eIF5A. This modification is catalyzed by two sequential enzymatic steps leading to the activation of eIF5A by the conversion of one conserved lysine to the unusual amino acid hypusine. The active translation factor facilitates the sequence-specific translation of polyproline sequences that otherwise cause ribosome stalling. In spite of the well-characterized involvement of active eIF5A in the translation of proline repeat-rich proteins, its biological role has been recently elucidated only in mammals, and it is poorly described at the functional level in plants. Here we describe the alterations in plant growth and development caused by RNAi-mediated conditional genetic inactivation of the hypusination pathway in Arabidopsis thaliana by knocking-down the enzyme deoxyhypusine synthase. We have uncovered that spermidine-mediated activation of eIF5A by hypusination is involved in several aspects of plant biology such as the control of flowering time, the aerial and root architecture and root hair growth. In addition this pathway is required for adaptation to challenging growth conditions such as high salt and high glucose medium and to elevated concentrations of the plant hormone ABA. We have also performed a bioinformatic analysis of polyproline-rich containing proteins as putative eIF5A targets to uncover their organization in clusters of protein networks to find molecular culprits for the disclosed phenotypes. This study represents a first attempt to provide a holistic view of the biological relevance of the spermidine-dependent hypusination pathway for plant growth and development.